DAMPAK KEPEMIMPINAN KOLABORATIF KEPALA SEKOLAH PEREMPUAN TERHADAP PARTISIPASI GURU DALAM PENGAMBILAN KEPUTUSAN: STUDI KASUS DI SDN 18 AMPENAN - Azizah, Yupiatul; Mustari, Mohammad (CV. Lafadz Jaya, 2024)
This research aims to explore the impact of female principals' collaborative leadership on teacher participation in decision making at SDN 18 Ampenan. The research method used is a qualitative approach with a case study design. Data was obtained through in-depth interviews, observation and policy documentation. The research results show an increase in teacher participation in school meetings, with more frequent and open discussions, as well as feelings of being valued in the decision-making process. The implementation of collaborative leadership has created a more democratic decision-making process and increased teachers' trust in school principals. Overall, this leadership style has a positive impact on teacher performance and productivity, as well as creating a more inclusive and harmonious work climate. This research confirms the important role of female school principals in building a collaborative culture that has an impact on improving the quality of education in schools, by facilitating the active involvement of teachers in decision making that is more transparent and oriented towards better results.